A FUZZY LOGIC ANALYSIS OF THE DISPARITY BETWEEN MAQASHID KNOWLEDGE AND ECONOMIC PRACTICE IN ISLAMIC EDUCATION - Muttaqin Sulaiman; Dedy Rachmad (Department Islamic Economics, 2025)
This study examines the critical gap between theoretical understanding of Maqashid Shariah and its practical implementation in economic activities within Islamic boarding schools (pesantren). Using a mixed-methods approach that integrates Al-Ghazālī’s maslahah theory and fuzzy logic linguistic analysis, the research analyzes data from 20 junior and senior high school students and one pesantren supervisor. The results reveal significant disparities, particularly at the senior high school level, where high conceptual understanding (fuzzy score 0.8) is not matched by adequate practical application (fuzzy score 0.9 in the “low” category). Fuzzy logic analysis maps the root problems to moderate curriculum effectiveness, limited practical programs, and weak evaluation mechanisms. These findings highlight the need for an integrative educational model that bridges the theory–practice gap through a maslahah-based approach and adaptive feedback systems.